2018
DOI: 10.1002/lt.25326
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Flush After Cold Storage as a New End‐Ischemic Ex Vivo Treatment for Liver Grafts Against Ischemia/Reperfusion Injury

Abstract: Cold storage (CS) remains the gold standard for organ preservation worldwide, although it is inevitably associated with ischemia/reperfusion injury (IRI). Molecular hydrogen (H ) is well known to have antioxidative properties. However, its unfavorable features, ie, inflammability, low solubility, and high tissue/substance permeability, have hampered its clinical application. To overcome such obstacles, we developed a novel reconditioning method for donor organs named hydrogen flush after cold storage (HyFACS),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 43 publications
1
11
0
Order By: Relevance
“…Previous methods for dissolving hydrogen in organ preservation solutions have involved generation of hydrogen by electrolysis [18,20,21,22] or by use of a hydrogen-generating agent [17], after which the hydrogen gas undergoes passive diffusion into the organ preservation solution. However, these methods are complicated and are unsuitable for clinical use Dissolving hydrogen gas in organ preservation solution with a hydrogen-absorbing alloy canister since it requires 24-48 hours for the hydrogen gas concentration in the solution to reach 1 mg/L.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous methods for dissolving hydrogen in organ preservation solutions have involved generation of hydrogen by electrolysis [18,20,21,22] or by use of a hydrogen-generating agent [17], after which the hydrogen gas undergoes passive diffusion into the organ preservation solution. However, these methods are complicated and are unsuitable for clinical use Dissolving hydrogen gas in organ preservation solution with a hydrogen-absorbing alloy canister since it requires 24-48 hours for the hydrogen gas concentration in the solution to reach 1 mg/L.…”
Section: Discussionmentioning
confidence: 99%
“…Use of hydrogen gas has been reported to be effective in transplantation models of various organs, including the small intestine [6][7], lung [8][9][10][11][12][13][14], liver [15][16][17][18], heart [19,20], osteochondral tissue [21], and kidney [22]. It is possible to expose the excised organ to hydrogen gas ex vivo without the donor and/or recipient inhaling the gas, and various methods have been devised to dissolve hydrogen gas in organ preservation solutions, including use of a hydrogen gas cylinder [6], electrolysis [18,20,21,22], or a hydrogen-generating agent [17]. However, these methods require bulky equipment and dangerous high-pressure cylinders with strict regulations for handling, resulting in the need to expend considerable time and effort for preparation.…”
Section: Introductionmentioning
confidence: 99%
“…In a human study, HW also significantly reduced liver fat accumulation in twelve overweight outpatients with NAFLD [ 111 ]. Another in vivo study revealed that oral HW significantly attenuated oxidative stress in patients with chronic hepatitis B [ 112 ]. In recent years, it has become widely accepted that bile acids are a nutrient signaling hormone [ 113 ].…”
Section: Preventive and Therapeutic Applications Of H 2 mentioning
confidence: 99%
“…Oxygen is supplied by the PV and the hepatic artery in half each. Therefore, in contrast to the brain, the liver has been regarded as the organ where inhaled H 2 is least likely to reach [16]. The liver is the largest organ in the body, performing a number of functions that are essential for life, such as metabolism, detoxification, and excretion, so protecting it with H 2 is considered to be a great advantage.…”
Section: Plos Onementioning
confidence: 99%